Pengaruh Fasilitas Bengkel dan Motivasi Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Shielded Metal Arc Welding (SMAW) Kelas XI Teknik Pemesinan SMK Negeri 5 Padang - Syukri Yolandi; Bulkia Rahim; Jasman; Eko Indrawan (Lembaga Yasin AlSys, 2026)
Workshop facilities and learning motivation are important factors in supporting the success of practical learning, particularly in the Shielded Metal Arc Welding (SMAW) subject at vocational high schools. This study aimed to analyze the effects of workshop facilities and learning motivation, both partially and simultaneously, on the learning outcomes of eleventh-grade Machining Engineering students in the SMAW subject at SMK Negeri 5 Padang. The study employed a quantitative approach with a correlational design and involved a population of 53 eleventh-grade Machining Engineering students from classes XI TP 1 and XI TP 2. Data were collected through questionnaires, documentation, and observation and were then analyzed using simple linear regression and multiple linear regression. The results showed that workshop facilities had a significant effect on students’ learning outcomes, with a calculated t-value of 9.672 and the regression equation Y = −28.155 + 1.720X₁. Learning motivation also had a significant effect on learning outcomes, with a calculated t-value of 9.378 and the regression equation Y = 28.32 + 10.61X₂. Simultaneously, workshop facilities and learning motivation had a positive and significant effect on students’ learning outcomes, with a coefficient of determination (R²) of 0.724 and the regression equation Y = 23.878 + 1.009X₁ + 0.578X₂. These findings confirm that adequate workshop facilities and high learning motivation jointly contribute to improving students’ learning outcomes in SMAW welding instruction. The implications of this study indicate the need for schools to improve the provision of practical facilities and foster students’ motivation through contextual and participatory learning strategies.